2004
DOI: 10.1105/tpc.016378
|View full text |Cite
|
Sign up to set email alerts
|

Storage Protein Accumulation in the Absence of the Vacuolar Processing Enzyme Family of Cysteine Proteases[W]

Abstract: The role(s) of specific proteases in seed protein processing is only vaguely understood; indeed, the overall role of processing in stable protein deposition has been the subject of more speculation than direct investigation. Seed-type members of the vacuolar processing enzyme (VPE) family were hypothesized to perform a unique function in seed protein processing, but we demonstrated previously that Asn-specific protein processing in developing Arabidopsis seeds occurs independently of this VPE activity. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
155
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(166 citation statements)
references
References 73 publications
7
155
2
1
Order By: Relevance
“…However, as observed before, the presence of MAT RNA does not necessarily result in the detection of the corresponding proteins. Additional cellular requirements and tissue-specific protein degradation determine high-level accumulation of MAT proteins (Gruis et al, 2004) Complementing the gain-of-function results, reduced expression of bZIP53 in a knockdown line that harbors a T-DNA insertion in the promoter leads to strong reduction in the expression of the corresponding target genes. However, these plants still set viable seeds, which might be due to a residual amount of bZIP53 protein.…”
Section: Bzip53 Constitutes a Transcriptional Regulator Of Seed Maturmentioning
confidence: 99%
“…However, as observed before, the presence of MAT RNA does not necessarily result in the detection of the corresponding proteins. Additional cellular requirements and tissue-specific protein degradation determine high-level accumulation of MAT proteins (Gruis et al, 2004) Complementing the gain-of-function results, reduced expression of bZIP53 in a knockdown line that harbors a T-DNA insertion in the promoter leads to strong reduction in the expression of the corresponding target genes. However, these plants still set viable seeds, which might be due to a residual amount of bZIP53 protein.…”
Section: Bzip53 Constitutes a Transcriptional Regulator Of Seed Maturmentioning
confidence: 99%
“…The Arabidopsis 2S albumins are exported from the ER as precursors that contain three propeptides (an N-terminal propeptide, an internal propeptide, and a C-terminal propeptide). These propeptides are removed posttranslationally by proteolytic processing enzymes (Gruis et al, 2002(Gruis et al, , 2004Shimada et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Quadruple aep null plants had a dramatically different seed protein profile, but this defective processing did not affect seed germination or the adult plant phenotype, which makes one wonder what the purpose of all this post-translational processing is? A close analysis of the proteins in aep null seeds showed that in the absence of AEP, rather than remain completely unprocessed the proalbumins (and proglobulins) were processed improperly and inaccurately by other proteases that otherwise played little or no role in albumin maturation (Shimada et al 2003b;Gruis et al 2004). Proteomic analysis of the albumin in Arabidopsis wild type and aep null plants also showed that one of the four Arabidopsis SEED STORAGE ALBUMIN (SESA) proteins was not fully dependent upon AEP for its maturation.…”
Section: Asparaginyl Endo-peptidasementioning
confidence: 99%
“…Arabidopsis aep2 mutants had mild defects in seed storage protein profile (Gruis et al 2002;Shimada et al 2003b). Single mutation in the other three AEP genes did not give noticeable changes in seed protein profile, but when lesions in AEP genes were pyramided the resulting plants had dramatically perturbed seed storage protein profiles (Shimada et al 2003b;Gruis et al 2004). Quadruple aep null plants had a dramatically different seed protein profile, but this defective processing did not affect seed germination or the adult plant phenotype, which makes one wonder what the purpose of all this post-translational processing is?…”
Section: Asparaginyl Endo-peptidasementioning
confidence: 99%
See 1 more Smart Citation